PATTERNS OF DILATORINESS FOR A CREDIT PRODUCT USING THE CART CLASSIFICATION TREE TECHNIQUE - Salinas Flores, Jesús (2005)
This study has the aim to find a pattern in delayed payments from the information obtained at the moment of requesting credit in a specific creditable product: At the same time, we show a very useful new statistical technique for this area, that is the classification tree (CART) that is applied in situations where we have independent predictor variables of classification or criterion that define the group to which every individual belongs. The paper also tries to find a set of decision rules that allow an explanation of the actual classification and the use of these rules to classify any new individual.